Robust Ordered Bundles of Porous Helical Nanotubes Assembled from Fully Rigid Ionic Benzene‐1, 3, 5‐tricarboxamides. Issue 43 (2nd September 2015) - Wu, Xibo; Wang, Daoliang; Chen, Mingming; Wei, Chengsha; Wei, Shenghui; Huang, Ningdong; Li, Liangbin; Zhang, Guobing
Abstract Size‐controlled and ordered assemblies of artificial nanotubes are promising for practical applications; however, the supramolecular assembly of such systems remains challenging. A novel strategy is proposed that can be used to reinforce intermolecular noncovalent interactions to construct hierarchical supramolecular structures with fixed sizes and long‐range ordering by introducing ionic terminals and fully rigid arms into benzene‐1, 3, 5‐tricarboxamide (BTA) molecules. A series of similar BTA molecules with distinct terminal groups and arm lengths are synthesized; all form hexagonal bundles of helical rosette nanotubes spontaneously in water. Despite differences in molecular packing, the dimensions and bundling of the supramolecular nanotubes show almost identical concentration dependence for all molecules. The similarities of the hierarchical assemblies, which tolerate certain molecular irregularities, can extend to properties such as the void ratio of the nanotubular wall. This is a rational strategy that can be used to achieve supramolecular nanotubes in aqueous environments with precise size and ordering at the same time as allowing molecular modifications for functionality.